The Role of Intellectual Education in Countering Extremism - Khalil, Prof.Dr. Waad Ibrahim Khalil (Sulaimani Journal for Humanities, 2026)
Teaching Islamic Education must be built upon the foundation of sharing homeland with partners including; individuals with whom we live, interact, and cooperate in order to achieve security and stability. It is therefore vital to begin this awareness at the primary school level by introducing students to a simplified understanding of the different social, religious, and cultural components that make up our community. This early exposure helps cultivate awareness of the religious, ethnic, and national diversity surrounding them.Through the proposal of this supplementary book, this study aims to contribute to intellectual education based on reason, analysis, cultural awareness, respect and acceptance of the other as a partner in the homeland. In doing so, we can put an end to the extremist ideas that distort the image of the other.By adopting an educational methodology rooted in rational thinking, logical analysis, and knowledge derived from facts and evidence, we can shape a generation of students who are curious, thoughtful, and independent in their pursuit of understanding in the future. It will encourage them to seek out information and reflect on it rather than simply receiving and being influenced by it, as is often the case now. This is a strategic scientific approach that focuses on knowledge and analysis, and it aligns with the global developments currently taking place in the field of education.
Keywords: education; thought; knowledge; extremism